Development of a self-directed learning model based on independence with a differentiation approach to improve higher order thinking skills of vocational high school students - Firdaus Firdaus; Sudarwan Danim; Manap Somantri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The Self Directed Learning Model is an independent activity that requires students to think critically and solve the problems. The aim of the research is to produce a Self-Directed Learning model based on independence with a differentiation approach to improve the higher order thinking skills of State Vocational School (SMK) students in North Bengkulu. The research uses the Research and Development method with a 4-D development model design consisting of definition, design, development and dissemination. The sample was chosen randomly and purposively sampling. Data collection uses questionnaires, interviews, validation and documentation. The results obtained in the research are an independence-based Self Directed Learning model that suits the needs of students at SMK Negeri 2 and SMK Negeri 5 North Bengkulu. The feasibility of the Independence-based Self Directed Learning model was validated by expert validators, vocational basics subject teachers.